The Effect of Service Quality, Facilities and Promotions on Guest Satisfaction at the Front Office of the Artotel Suites Mangkuluhur Hotel Department Jakarta - Pahlevi, Muhammad Mirza; Kusumaningrum, Anisa Putri; Pradini, Gagih (International Journal of Education, Information Technology, and Others, 2025)
This research aims to determine various factors that influence guest satisfaction at the front office department of the Hotel Artotel Suites Mangkuluhur Jakarta. The factors studied include service quality, facilities and promotions. This research involved a sample of 100 respondents, who were guests of the Artotel Suites Mangkuluhur Jakarta Hotel. The research method used is a quantitative method with data collection through questionnaires and analysis using appropriate statistical techniques, namely SPSS version 25. The research results show that the service quality variable has a positive and significant influence on guest satisfaction, the facility variable also has a positive and significant influence on guest satisfaction and the promotion variable has a positive and significant influence on guest satisfaction. Likewise, in tests carried out jointly, the variables of service quality, facilities and promotions had a positive and significant influence on guest satisfaction at the Artotel Suites Mangkuluhur Jakarta Hotel.